Challenges and solutions for implementing telemedicine in Iran from health policymakers' perspective - Seyed Mojtaba Hosseini; Shiva Abdolahnejad Boushehri; Khalil Alimohammadzadeh (BMC, 2024)
Abstract Background Despite significant progress in health technology and growing interest among countries in incorporating telemedicine into healthcare delivery, its usage remains limited in Iran. The aim of this study is to investigate the challenges related to telemedicine in Iran and pinpoint potential solutions from the viewpoint of health policymakers, marking the first such endeavor. Methods This qualitative study was conducted in Iran in 2022. Data were gathered from 19 health policymakers who were selected using purposeful and snowball sampling techniques via in-depth and semi-structured interviews. The research findings were analyzed using the content analysis technique, with coding performed using MAXQDA software. The content analysis approach developed by Erlingsson was utilized to analyze the data. Results The study revealed eight main challenges that inhibit the widespread use of telemedicine in Iran. These challenges include policy weaknesses, uncertainty around operating mechanisms, inadequate communication and telecommunication infrastructure, insufficient cultural infrastructure, lack of electronic requirements, redundant bureaucracies, legal gaps, and economic factors. Furthermore, four key solutions to these challenges were identified. These include a national commitment to the development of telemedicine, the establishment of a telemedicine roadmap, the enhancement of e-health requirements and infrastructure, and the preparation of the community to accept telemedicine as a viable option for healthcare delivery. Conclusion The implementation of telemedicine in Iran faces significant challenges, some of which are related to the national healthcare system, while others stem from various policy-related institutions and organizations. Addressing these challenges will require extensive inter-organizational cooperation and strong leadership at the governance level. However, it should be noted that fully resolving these issues is a time-consuming process.